(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Background: Distance learning is gaining special significance today, as with the development of the Internet and students owning personal computers, the information exchange between teachers and students is improving. Objectives: The current study aims at investigating the reality of educational platforms in distance education during the COVID-19 pandemic and their impact on academic achievement before and after the COVID-19 pandemic from the viewpoint of Tabuk University students. Methods: The study sample consisted of (1000) students from Tabuk University divided into (427) males and (573) females of all levels of education. The researcher used the correlational descriptive-survey research method. Result: The demographic study showed that there were statistically significant differences in the scale of educational platforms in distance education during the COVID-19 Pandemic at the University of Tabuk. Further, the pandemic has increased the flow of distance learning in educational institutes in Saudi Arabia. Conclusion: Future studies should also be conducted to explore the impacts of advanced technologies on the training and development of connections in the education sector.